Implementasi Metode Prototype pada Rancang Bangun Sistem Pendukung Keputusan Pemilihan Mahasiswa Berprestasi Berbasis Web - Husni Angriani; Yeni Saharaeni; Hasniati Hasniati (Jurnal INSYPRO (Information System and Processing), 2023)
The selection of outstanding students can be an important factor in awarding scholarships at the university level. However, in some cases, the process of selecting outstanding students and awarding scholarships is considered to be less objective, resulting in scholarships being awarded to students who may not necessarily be the most deserving. To address this issue, a system for selecting outstanding students was developed at STMIK KHARISMA Makassar to help all stakeholders in the institution make a more objective selection. The system is web-based and can be accessed in real-time by all stakeholders. The prototype method was used to help stakeholders and software engineers describe the software's requirements and specifications. The implementation of the system showed that it can assist in the evaluation process objectively based on the criteria set by all stakeholders, and that all system specifications are relevant to the user requirements. In conclusion, the development of this system has the potential to improve the selection process for outstanding students and ensure that scholarships are awarded to the most deserving students. By providing a more objective and transparent process, this system can help ensure that awards and scholarships are awarded on target.